Assessing Spectrum of Fractures in Elderly; Perspective on Tertiary Care Hospital of Nepal - Parajuli, B; Sharma, R; Kayastha, SR; Thapa, J; Shrestha, R; Shrestha, D (Kathmandu University Medical Journal, 2023)
Background There is an increasing life expectancy and a surging elderly population in the last few decades, leading to a higher incidence of fractures in the elderly. The health care of the elderly in Nepal is below par and there are no studies done to evaluate the spectrum of fractures in the elderly. Objective To evaluate the demographical and epidemiological aspects of fractures in the elderly (≥ 65 years) presenting to a tertiary care hospital in Nepal in a 15 years’ timeline. Method This study was a retrospective epidemiological study conducted in the Department of Orthopedics, Dhulikhel Hospital, Kathmandu University Hospital (DH, KUH), Nepal. The patients of age ≥ 65 years having traumatic injuries, admitted in the orthopedics ward from 2006 January to 2020 December were included. Patient demographics, site of injury, fracture incidence, mechanism of injury, hospital stay duration, and mode of treatment (surgical/ conservative) were evaluated. Result Of the 787 patients with an average age of 73.65 ± 7.5 years, 54% were females. Peritrochanteric fracture was the most common fracture (29.4%) followed by spine (18.3%). The most common mechanism of injury was fall on the labeled ground (38.6%). The incidence of fragility fractures (peri-trochanteric, proximal humerus, spine, and distal radius) was increasing with age. Conclusion Females, peritrochantric fractures, and trivial trauma are the most common occurrences for fractures in elderly. The incidence of fragility fractures is increasing with age but the overall incidence of fractures compared to other studies is low. Higher incidences of road traffic accidents (RTA) and compound fractures among the elderly are serious public health concerns that highlight the importance of primary preventive measures.